School effectiveness or the horizon of the world as a laboratory - Normand, Romuald (British Journal of Sociology of Education, 2008)
The present paper aims to provide an account of the genesis and development of a collection of scientific work that has received strong international recognition – the paradigm of school effectiveness. It shows how this theory, based on the design of measurement tools, has gradually influenced educational management and policies in promoting the effectiveness and quality of educational systems. In mobilising allies, setting up laboratories and extending its networks into major international organisations, school effectiveness research has contributed to the emergence of a new form of governance of education systems at a European level and to the promotion of new assessment methods of research in education.
Publisher: Routledge _eprint: https://doi.org/10.1080/01425690802423346
Keywords: assessment; effectiveness; indicators; networks; policy; science